2014
DOI: 10.3109/02813432.2014.929819
|View full text |Cite
|
Sign up to set email alerts
|

Importance of healthcare utilization and multimorbidity level in choosing a primary care provider in Sweden

Abstract: Objective. To study the associations between active choice of primary care provider and healthcare utilization, multimorbidity, age, and sex, comparing data from primary care and all healthcare in a Swedish population. Design. Descriptive cross-sectional study using descriptive analyses including t-test, correlations, and logistic regression modelling in four separate models. Setting and subjects. The population (151 731) and all healthcare in Blekinge in 2007. Main outcome measure. Actively or passively liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
10
1
2
Order By: Relevance
“…But usefulness of such a valid model is manifold, i.e. in understanding the pro CAM decision, predicting such choice and decision, formulating healthcare strategies and development of health human resource accordingly [19,20]. The study by Fouladbakhsh and Stommel [21] took socio-behavioural model (SBM) guided by Andersen as baseline of determining the choice dynamics of CAM in cancer and non-cancerous patients.…”
Section: Discussionmentioning
confidence: 99%
“…But usefulness of such a valid model is manifold, i.e. in understanding the pro CAM decision, predicting such choice and decision, formulating healthcare strategies and development of health human resource accordingly [19,20]. The study by Fouladbakhsh and Stommel [21] took socio-behavioural model (SBM) guided by Andersen as baseline of determining the choice dynamics of CAM in cancer and non-cancerous patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly women are more often hospitalised, have longer stays at hospitals and have higher rates of most chronic diseases than men [ 22 ]. Other studies from Blekinge County showed that multimorbidity level is positively correlated with number of consultations in PHC [ 23 ], and that women and individuals with higher multimorbidity level were more often actively listed at PHC [ 23 , 24 ]. In our study we found that even home health care utilisation is associated with multimorbidity level and gender, especially in older women.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In a previous paper, we found that more consultations, higher multimorbidity level, older age and female gender were positively associated with active listing in primary care. 26 Here we combined these factors with socioeconomic status, type of primary care practice and geographical factors, and we found that multimorbidity level, age and geographical location contributed most to active listing and that type of primary care practice contributes more than socioeconomic status and distances to healthcare.…”
Section: Discussionmentioning
confidence: 97%